Modelos de realizações discursivas nos benditos populares e nas novenas - Gomes, Camila Maria (2014)
With the purpose of contribute to the understanding of oral texts constituent processes, we seek, with this work, verify how formulaicity processes in the benditos and novenas , religious intangible heritage, are established. For this, we made an overview on the performance of repetitions which are established in the corpus collected for the study, considering the presence of Discourse Traditions in the analyzed texts. It is noteworthy that the corpus consists of benditos and novenas collected in the municipality of Lajes, Rio Grande do Norte. This material is part of the differential corpus of the Project for the History of Brazilian Portuguese (PHPB-RN). Regarding the theoretical framework used to guide the research, we based our analysis on Discourse Traditions (DTs) theoretical assumptions, with the ideas defended by Johannes Kabatek, besides taking into consideration the assumptions of Paul Zumthor about orality in popular religious texts, among other authors cited throughout the work. In the context of popular cultures, the existence of oral texts serves to various interactive objects and this is not different in popular benditos and novenas (cf. Sá Júnior, 2009). In this sense, focusing the gaze through Discourse Traditions (DTs), we can verify that the texts/discourses present discursive regularities or textual forms already produced by society, in earlier times, which remain or are modified throughout its existence, as shows Johannes Kabatek (2001, 2003, 2005 and 2006). Also in this sense, Paul Zumthor (1993) presents us the idea that talk about using "word" in memory, in its real sense, implies admitting it as something which has an immeasurable power, which is able to decide directions in world, and from that is established the "wealth of oral traditions"